ANALISIS PENGEMBANGAN UMKM DALAM MENINGKATKAN KESEJAHTERAAN MASYARAAKAT DI DESA KOTING B - Angela Margaretha Theresia Weni; Maria Nona Dince; Paulus Libu Lamawitak (Universitas Nusa Nipa Maumere, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in enhancing community economic growth. Good economic growth serves as an indicator of the government’s success in implementing development programs. This research aimed to analyze the development of MSMEs, particularly in Koting B Village, focusing on two indicators, namely, business development, which covers health, education, employment, and housing. The research used a descriptive qualitative approach using observation, interviews, and documentation techniques. The findings revealed that MSMEs actors have undertaken various efforts to develop their businesses, such as obtaining capital loans, determining selling prices, and enhancing marketing activities. The existence of MSMEs helped communities meet additional family economic needs. The results also indicated that village government support need to be further optimized, particularly in terms of access to capital, human resources, and marketing through the utilization of digital platforms, to improve the competitiveness of MSMEs so they can continue to grow and make a significant contribution to national economic growth.